E-012 Endovascular biopsy of vertebrobasilar aneurysm demonstrates differential expression of immunologic genes in polyarteritis nodosa patient. (4th August 2020) - Narsinh, K; Narsinh, K; McCoy, D; Sun, Z; Winkler, E; Abla, A; Cooke, D
Abstract : Introduction: Personalized medicine refers to the practice of tailoring intervention to an individual based on their unique genotypic or phenotypic characteristics. Gene expression analysis of aneurysms compared to normal arteries is difficult because of risks associated with tissue collection. Endovascular biopsy is a low-risk alternative method for collecting endothelial cells from aneurysms and comparing them to the same patient's non-aneurysmal endothelial cells. Methods: A patient with a large, fusiform, partially thrombosed vertebrobasilar artery aneurysm was recruited for research study after institutional review board approval. We used simple endovascular techniques to collect cells from the patient's vertebrobasilar artery aneurysm and their femoral artery during flow-diverting stent placement. The biopsied cells underwent fluorescence-activated cell sorting (FACS) to isolate viable endotheilal cells. Then, RNA was extracted and cDNA libraries generated using the Smart-seq2 protocol on the Fluidigm C1 platform, followed by sequencing using a Illumina HiSeq2500. Gene expression levels were calculated and filtered as read per kilobase per million mapped reads (RPKM). Principal component analysis, differential gene expression analysis, gene ontology and biological pathway analysis was performed to identify candidate genes and expression pathways related to disease pathogenesis and potential medical therapy. Results: Flow-diverting stents were placed in the ipsilateral vertebral artery, and the contralateral vertebral artery was occluded using coils. The vertebrobasilar aneurysm continued to grow and the patient suffered worsening mass effect on the brainstem before entering hospice care. Gene expression analysis identified significant differences in human leukocyte antigen gene complex series (HLAs) and interferon signaling exonuclease genes, implicating a strong role for the immune system in the progression of this patient's aneurysms. In parallel, the patient underwent occipital artery to anterior inferior cerebellar artery (AICA) bypass to treat a separate AICA aneurysm. Histologic evaluation of a resected occipital artery segment demonstrated necrotizing transmural vasculitis compatible with polyarteritis nodosa. Conclusion: Endovascular biopsy can be performed to obtain aneurysmal tissue with low risk. Analysis of the collected endothelial cells may yield insight into disease pathogenesis and therapeutic alternatives. Disclosures: K. Narsinh: None. K. Narsinh: None. D. McCoy: None. Z. Sun: None. E. Winkler: None. A. Abla: None. D. Cooke: None.